Binding kinetics and structural analysis of chickpea protein interactions with spent coffee phenolics under varying pH and concentrations - Saricaoglu, Beyza; Yılmaz, Hilal; Subasi, Busra Gultekin; Mohammadifar, Mohammad Amin; Capanoglu, Esra; Yılmaz, Hilal (Elsevier, 2024)
Several studies have been performed to improve structural, nutritional and functional properties of proteins through protein-phenolic interactions. In this study, changes in the structure of chickpea protein following interaction with spent coffee phenolics were analyzed. Varying phenolic concentrations (0, 0.5, 1.0, and 1.5) and pH values (7.0 and 9.0) were examined to investigate the effect of different interaction conditions. The results indicated that spent coffee phenolics induced the secondary and tertiary structure of chickpea protein, and this change was affected by the phenolic concentration. The interaction with phenolic compounds resulted in a blue shift in the FTIR spectra in Amide A at both pH values. Chickpea protein isolate (CPI) reacted with phenolic compounds via C-N and N-H bonds and hydrogen bonds were built up between protein-phenolic complexes. Thermodynamic parameter calculations indicated that hydrogen bonding and van der Waals forces were the primary types of interactions between CPI and phenolic extract at both pH conditions (7.0 and 9.0). Besides, irregularity of shapes was observed in morphological analysis after protein-phenolic interaction. In addition to proven structural changes, this study has laid the basis for future studies investigating the effect of phenolics on the functional and nutritional properties of chickpea proteins.
Keywords: Protein-Phenolic Interaction; Plant-Based Protein; Protein Structure; Fluorescence Spectroscopy; Protein Modification